Retinol Isotope Dilution Is Applied during Restriction of Vitamin A Intake to Predict Individual Subject Total Body Vitamin A Stores at Isotopic Equilibrium. Issue 11 (28th September 2016) - Green, Michael H; Ford, Jennifer Lynn; Green, Joanne Balmer
Abstract: Background: Retinol isotope dilution (RID) equations are used to determine vitamin A status and the efficacy of vitamin A intervention programs. Recent work related to RID methods has focused on modifying the "Olson equation" to improve the accuracy of predictions of vitamin A total body stores (TBS) in individual subjects. Objective: We investigated the hypothesis that short-term restriction of vitamin A intake would result in accurate RID prediction of vitamin A TBS in individuals. Methods: We applied model-based compartmental analysis to a 6-component model derived from published retinol kinetic studies on 12 individuals with a wide range of vitamin A stores and determined vitamin A TBS in the steady state. Then we simulated the impact of eliminating or strictly limiting vitamin A intake at the time of isotope administration, while maintaining plasma retinol homeostasis, on retinol specific activity in plasma (SAp ; fraction of dose/μmol retinol) and stores, and we calculated TBS using the simplified RID equation TBS = 0.75 × 1/SAp, where the fractional absorption of tracer was set at 0.75 and SAp was simulated 5 d after dosing. Results: When vitamin A intake was zero or strictly limited (0.25 μmol/d), mean TBS predicted by the equation at 5 d after dose administration divided by TBS determined by using the model was 1.00 (range: 0.959–1.04) or 1.02 (range: 0.983 – 1.06), respectively. Conclusions: By eliminating or strictly limiting vitamin A input, isotopic equilibrium was reached by 5 d. At isotopic equilibrium, SAp is the same as that in the body's exchangeable vitamin A pools; under these conditions, SAp may be measured at any time from 5 d on and used to calculate TBS.